Early-onset Neonatal Pneumococcal Sepsis: A Fatal Case Report and Brief Literature Review. Issue 4 (April 2018) - Jarovsky, Daniel; Marchetti, Ivan Cese; da Silva Mori, Mariana Alves; de Souza, Ricardo Magalhães; Almeida, Flávia Jacqueline; Sáfadi, Marco Aurélio Palazzi; Berezin, Eitan Naaman
Abstract : Sepsis caused by Streptococcus pneumoniae is rare in neonates although associated with high morbidity and mortality. We report a fatal case of invasive pneumococcal disease in a term neonate whose mother was healthy and did not receive any pneumococcal vaccine. Investigation of the infection source yielded negative results. Acquisition of infection through the birth canal was considered unlikely. Abstract : Supplemental Digital Content is available in the text.